More sun, less myopia: validating CUVAF as a biomarker for outdoor exposure in a cohort of Spanish schoolchildren - De La Puente, Miriam; Irigoyen-Bañegil, Cristina; Dosal-Franco, Macarena; Llorente-Gonzalez, Sara; Bilbao-Malavé, Valentina; Vinolas-Parcet, Martí; Bezunartea, Jaione; Hernández, María; Fernández-Robredo, Patricia; Martín-Calvo, Nerea; García-Layana, Alfredo; González-Zamora, Jorge; et al. (Frontiers in Medicine, 2026)
IntroductionThe increasing global prevalence of childhood myopia has become a significant public health concern. Among environmental risk factors, reduced outdoor activity (OA) has been consistently associated with a higher incidence of myopia. While questionnaires are traditionally used to estimate sunlight exposure, conjunctival ultraviolet autofluorescence (CUVAF) has emerged as an objective biomarker for cumulative ocular UV exposure.MethodsA cross-sectional case–control study was conducted among 2,616 children aged 7–8 and 11–12 years from 39 schools in Madrid, Spain. After reviewing the exclusion criteria, 354 children were removed from the study, leaving 2,262 participants in the sample. Participants were classified based on refractive error and underwent ocular examination and lifestyle questionnaires. The CUVAF area was measured in 1,129 children for logistical reasons, and they were grouped according to weekly time spent in OA (<7 vs. ≥7 h). Multivariate logistic regression and ROC curve analyses were performed to assess associations between OA, CUVAF, and myopia.ResultsMyopia prevalence was significantly lower in children spending ≥7 h per week in OA than those with less exposure (9% vs. 18%; p < 0.001). CUVAF presence was strongly associated with higher OA and lower prevalence of myopia. A negative correlation was observed between CUVAF and myopia across schools (r = −0.6; p < 0.05). A diagnostic model using age-adjusted CUVAF showed a 91.9% probability of being non-myopic (negative predictive value) (positive predictive value: 10.79%; sensitivity: 76.5%; specificity: 29.6%). Each additional hour of OA reduced myopia risk by 2% (OR = 0.98; p = 0.01), while ≥7 h weekly halved the risk (OR = 0.50; p < 0.001). Conversely, the prevalence of high CUVAF increased with greater OA (OR = 2.54 for ≥7 h/week).ConclusionCUVAF is a reliable, objective, and non-invasive biomarker of outdoor light exposure that correlates inversely with myopia in children. The larger sample size of this study supports the potential clinical utility of CUVAF not only for evaluating an individual’s risk of myopia development during childhood but also for monitoring adherence to lifestyle modifications aimed at its prevention. Its integration into routine screening could improve early detection and personalized prevention strategies for childhood myopia.